Emergence of Emotions in Politics: A Historical Perspective - Akbar, Nabeila; Shabbir, Asma (Annals of Human and Social Sciences, 2024)
The function of emotions in politics is not a recent thing and was an element of theoretical studies until the Age of Reason. Then sentiments and feelings were disregarded in studies until the 1980s. Sentiments and feelings have recently resurfaced in studies. A deep understanding of emotions and politics is required to comprehend national and international system. The main objective of the present study is to investigate the relationship between the emotions and politics. The study examines the influence of emotions in contemporary politics. The study utilizes qualitative research methods to analyze the role of emotions. This research paper is historical, descriptive and analytical. Data will be collected from secondary sources, books, articles and journals. By analyzing Social Identity Theory, the research paper explores that societal identification that emerges from the sharing of political thoughts and opinions becomes political via the actions of group ruling members. The result shows that human feelings and emotions have a tremendous impact on politics, where the society has been split into groups such as caste, bridari, and tribes.